The prevalence of Legionella and mycoplasma seropositivity in the elderly in Cape Town - Muller, Greta (Division of Geriatric Medicine, 2017)
Background: Community acquired pneumonia causes 5,9% of deaths in elderly South Africans. Mortality rates are increased in those in whom initiation of therapy with an appropriate agent has been delayed. Whereas Mycoplasma pneumoniae and Legionella pneumophila are sensitive to the macrolides or tetracycline, they do not respond to the currently recommended first-line agents for community acquired pneumonia, penicillin or a cephalosporin. It was therefore necessary to assess the prevalence of exposure to these 2 organisms in the elderly in order to determine whether a modification in the recommendations may be justified. Methods: Study population and survey: Subjects were residents of 4 old age homes in Cape Town who were older than 60 years and willing to participate. Written consent was obtained, a demographic and medical history questionnaire was completed, and a sample of blood was drawn. Laboratory methods: The indirect fluorescent antibody tests (Zeus Scientific Inc, New Jersey, USA) were used to detect the presence of antibodies to Mycoplasma pneumoniae and Legionella pneumophila. Results: The participation rate in this study was high, with 88,4% (677/766) taking part. Seropositivity for both of these organisms was low. There were 17 participants (2, 51 %) with antibodies to mycoplasma (IgG only in 8, IgM only in 1, and both IgG and IgM in the remaining 8). Titres were low with only 1 IgM titre of 16, and only 3 IgG titres of 64. Antibodies to Legionella were demonstrated in only 9 participants (1,33%). All these titres were 128 or above. Conclusions: It is concluded that first-line therapy for community acquired pneumonia should adhere to the current guidelines published by the South African Pulmonology Society. There is no indication for the routine use of agents active against Legionella or mycoplasma. Clearly, these antibiotics should be introduced if specific pointers to infection with one of these organisms are found. Because of the low seropositivity rate, the indirect fluorescent antibody test for these 2 agents has a high specificity in this population. This may be of use in making a diagnosis in an acute infection Further studies are required to elucidate the immunological response to these organisms in elderly persons. A further survey should be done to determine the seropositivity rate to these agents in community dwelling elderly.